Tourism in Times of Crisis and Post-Crisis: A Model to Understand Tourists' Post-Pandemic Travel Intentions - Salman, Ahmad; Trupp, Alexander *; Chan, Ling Foon * (Institute for Tourism, 2024)
The COVID-19 pandemic has had a profound effect on tourists' travel plans. Whilst the relationship between perceived risk and tourists' decisions and behaviours concerning COVID-19 is already an established research area in tourism studies, the dynamics of post-pandemic travel intentions and how they are influenced by travel motivation, destination safety and the notion of revenge tourism received very little attention. Therefore, this study proposes a model linking revenge tourism, destination safety, and travel motivations, leading to post-pandemic travel intentions. Furthermore, this research note lays a foundation for future research that can guide towards understanding tourists' travel intentions in times of crisis, similar to the COVID-19 pandemic.